Search for chargino-neutralino pair production in final states with three leptons and missing transverse momentum in √s = 13 TeV pp collisions with the ATLAS detector - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (The European physical journal. C, Particles and fields, 2021)
A search for chargino-neutralino pair production in three-lepton final states with missing transverse momentum is presented. The study is based on a dataset of √s = 13 TeV pp collisions recorded with the ATLAS detector at the LHC, corresponding to an integrated luminosity of 139 fb-. No significant excess relative to the Standard Model predictions is found in data. The results are interpreted in simplified models of supersymmetry, and statistically combined with results from a previous ATLAS search for compressed spectra in two-lepton final states. Various scenarios for the production and decay of charginos ( ̃χ ±) and neutralinos ( ̃χ 02) are considered. For pure higgsino χ ± 1 ̃χ 02 air-production scenarios, exclusion limits at 95% confidence level are set on χ 02masses up to 210 GeV. Limits are also set for pure wino χ ±1 ̃χ 02 air production, on ̃χ 02 masses up to 640 GeV for decays via on-shell W and Z bosons, up to 300 GeV for decays via off-shell W and Z bosons, and up to 190 GeV for decays via W and Standard Model Higgs bosons.